2001
DOI: 10.1016/s0014-5793(01)02622-9
|View full text |Cite
|
Sign up to set email alerts
|

Furin and membrane type‐1 metalloproteinase mRNA levels and activation of metalloproteinase‐2 are associated with arterial remodeling

Abstract: Matrix metalloproteinase (MMP) activation is an essential feature of pathological and physiological arterial enlargement or shrinkage. Recently, furin-activated membrane type-1 MMP (MT1-MMP) was identified as the in vivo activator of MMP2 in mice. Although arterial enlargement and shrinkage are important in several pathological processes, this proprotein convertase^MT1-MMP axis has not been described during arterial remodeling. In rabbit femoral and carotid arteries, we report an increase in furin and MT1-MMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 26 publications
1
32
0
1
Order By: Relevance
“…have shown that proMT1-MMP has to be processed to activate MMP2 (Pei and Weiss, 1996;Yu et al, 1997;Cao et al, 1998;Yana and Weiss, 2000). Recently, several laboratories have generated a wealth of data showing strong correlations between furin activity and those of MT1-MMP and MMP2 (Maquoi et al, 1998;Bassi et al, 2001;de Kleijn et al, 2001). Moreover, several groups have found proMT1-MMP at the plasma membrane of different cell lines, adding weight to the proposition that the pro-domain of MT1-MMP is required for the efficient trafficking of the enzyme to the cell surface (Sato et al, 1994;Sternlicht and Werb, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have shown that proMT1-MMP has to be processed to activate MMP2 (Pei and Weiss, 1996;Yu et al, 1997;Cao et al, 1998;Yana and Weiss, 2000). Recently, several laboratories have generated a wealth of data showing strong correlations between furin activity and those of MT1-MMP and MMP2 (Maquoi et al, 1998;Bassi et al, 2001;de Kleijn et al, 2001). Moreover, several groups have found proMT1-MMP at the plasma membrane of different cell lines, adding weight to the proposition that the pro-domain of MT1-MMP is required for the efficient trafficking of the enzyme to the cell surface (Sato et al, 1994;Sternlicht and Werb, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been demonstrated that full-length proMT1-MMP is the prominent form appearing at the plasma membrane of many cell types, the subcellular site of activation and the identity of the activating enzyme remain controversial (Sato et al, 1994;Okumura et al, 1997;Cao et al, 1998;Lehti et al, 1998;Sternlicht and Werb, 2001). Nonetheless, a proprotein-convertase/MT1-MMP/MMP2 axis has been proposed to conduct ECM remodeling (Yana and Weiss, 2000;de Kleijn et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…47 It is still unclear how the vascular wall senses these biomechanical effects, but the endothelium plays an important role in its response. 1 Flow changes can upregulate activation of MMPs, 48 which are considered to be important for remodeling in general. 49,50,26 Endothelial cells sense shear stress and various patterns of flow by regulating the expression of intracellular adhesion molecule 1, vascular adhesion molecule 1, 51 monocyte chemoattractant molecule 1, 52 and MMP-9.…”
Section: Expansive Remodeling: a Role For Innate Immunity?mentioning
confidence: 99%
“…Matrix turnover in arteries occurs during arterial remodeling in response to sustained blood flow changes, 11,12 balloon injury, 13,14 and atherosclerotic plaque formation. 15 Arterial remodeling, which can be outward to reduce lumen loss and inward to increase lumen loss, is characterized by structural changes of the arterial wall involving cell migration and collagen (matrix) breakdown 16 by matrix metalloproteases (MMPs), including MMP9, which can be stimulated by Tlr4 activation.…”
mentioning
confidence: 99%